Increasing GLP-1 Circulating Levels by Bariatric Surgery or by GLP-1 Receptor Agonists Therapy: Why Are the Clinical Consequences so Different? - Chloé Amouyal; Fabrizio Andreelli (Journal of Diabetes Research)
The “incretin effect” is used to describe the observation that more insulin is secreted after the oral administration of glucose compared to that after the intravenous administration of the same amount of glucose. During the absorption of meals, the gut is thought to regulate insulin secretion by secreting a specific factor that targets pancreatic beta cells. Additional research confirmed this hypothesis with the discovery of two hormones called incretins: gastric inhibitory peptide (GIP) and glucagon-like peptide 1 (GLP-1). During meals, specific cells in the gut (L and K enteroendocrine cells) secrete incretins, causing an increase in the blood concentrations of, respectively, GLP-1 and GIP. Bariatric surgery is now proposed during the therapeutic management of type 2 diabetes in obese or overweight populations. It has been hypothesized that restoration of endogenous GLP-1 secretion after the surgery may contribute to the postsurgical resolution of diabetes. In 2005, the commercialization of GLP-1 receptor agonists gave the possibility to test this hypothesis. A few years later, it is now accepted that GLP-1 receptor agonists and bariatric surgery differently improve type 2 diabetes. These differences between endogenous and exogenous GLP-1 on glucose homeostasis emphasized the dual properties of GLP-1 as a peptide hormone and as a neurotransmitter.